Nontargeted quantitation of lipid classes using hydrophilic interaction liquid chromatography-electrospray ionization mass spectrometry with single internal standard and response factor approach - Cífková, Eva; Holčapek, Michal; Lísa, Miroslav; Ovčačíková, Magdaléna; Lyčka, Antonín; Lynen, Frédéric; Sandra, Pat (Analytical chemistry, 2012)
The identification and quantitation of a wide range of lipids in complex biological samples is an essential requirement for the lipidomic studies. High-performance liquid chromatography-mass spectrometry (HPLC/MS) has the highest potential to obtain detailed information on the whole lipidome, but the reliable quantitation of multiple lipid classes is still a challenging task. In this work, we describe a new method for the nontargeted quantitation of polar lipid classes separated by hydrophilic interaction liquid chromatography (HILIC) followed by positive-ion electrospray ionization mass spectrometry (ESI-MS) using a single internal lipid standard to which all class specific response factors (RFs) are related to. The developed method enables the nontargeted quantitation of lipid classes and molecules inside these classes in contrast to the conventional targeted quantitation, which is based on predefined selected reaction monitoring (SRM) transitions for selected lipids only. In the nontargeted quantitation method described here, concentrations of lipid classes are obtained by the peak integration in HILIC chromatograms multiplied by their RFs related to the single internal standard (i.e., sphingosyl PE, d17:1/12:0) used as common reference for all polar lipid classes. The accuracy, reproducibility and robustness of the method have been checked by various means: (1) the comparison with conventional lipidomic quantitation using SRM scans on a triple quadrupole (QqQ) mass analyzer, (2) (31)P nuclear magnetic resonance (NMR) quantitation of the total lipid extract, (3) method robustness test using subsequent measurements by three different persons, (4) method transfer to different HPLC/MS systems using different chromatographic conditions, and (5) comparison with previously published results for identical samples, especially human reference plasma from the National Institute of Standards and Technology (NIST human plasma). Results on human plasma, egg yolk and porcine liver extracts are presented and discussed.